The Effectiveness of Social Studies Learning based on Local Wisdom on Strengthening the Character of Elementary School Students - Azizah Latifah; Aulia Fitriani; Oman Farhurohman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, Jurusan Tarbiyah dan Keguruan, Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This study aims to analyze the effectiveness of Social Science (IPS) learning based on local wisdom in strengthening the character of elementary school students. The method used is Systematic Literature Review (SLR) on various relevant national researches. The results of the study show that the application of local cultural values through folklore, traditional games, and culture-based media is effective in increasing social understanding and instilling the character of mutual cooperation, responsibility, and love for the homeland. This approach makes learning more contextual and meaningful according to students' lives. However, its implementation still faces obstacles, such as limited teacher competence, lack of local teaching materials, and school policy support. Therefore, teacher training, the development of contextual learning resources, and the synergy of schools and communities in preserving cultural values are needed.